Identification and molecular analysis of 11 cases of the PTS gene variants associated with tetrahydrobiopterin deficiency - Li, Lulu; Yang, Haihe; Zhao, Jinqi; Yang, Nan; Gong, Lifei; Tang, Yue; Kong, Yuanyuan (Frontiers in Genetics, 2022)
Background: Tetrahydrobiopterin deficiency (BH4D) is a rare autosomal recessive amino acid metabolic disease, belongs to a kind of hyperphenylalaninemia (HPA), and 6-pyruvyltetrahydrotrexate synthase (PTPS) deficiency is the most common type of BH4D. This study investigates the clinical and genetic characteristics of 11 PTPS deficiency cases in Beijing area, identifies the genetic pathogenic factors, and evaluates the value of high-throughput sequencing in the precise diagnosis of PTPS deficiency. Methods: Beijing Neonatal Disease Screening Center diagnosed patients with HPA. The study used phenylalanine (Phe) in blood, the ratio of Phe to Thr, urinary trexate spectrum analysis, erythrocyte dihydrotrexate reductase (DHPR) activity determination and High-throughput sequencing as methods. Bioinformatics software analyzed the variants' pathogenicity, and used RT-PCR to identify deep intron variation's pathogenicity. Result: Among 635 cases with HPA, 38 cases were diagnosed with BH4D, which the incidence in HPA was 5.98%. Nine kinds of PTS gene variants were detected, including seven missense variants, one splicing variant and one deletion variant. The splicing variant c.84-291A>G had three splicing results in vivo: normal length, exon 3 skipping, 79bp pseudoexon insertion and exon 3 skipping. Bioinformatics and sanger sequencing were performed to verify the identified variants. Conclusions: High-throughput sequencing is a helpful tool for clinical diagnosis and differential diagnosis of BH4D. This study confirms that c.84-291A>G is the hot spot variant of PTPS deficiency, and it is the first reported variant with a new splicing pattern in vivo. A novel deletion variant c.84_163del (p.Lys29Cysfs*9) is found to enrich the genetic variant spectrum of the disease.